Implementation of the Dimensions of Smart Organization and its Relation to the Level of Technical Innovation in Palestine Technical College - Deir Al Balah from the Staff's Perspectives - Mervat Mohammed Rady; Diana Abdunnasser Abu Shammale; Shaima' Mosa Hania (University of Science and Technology, Yemen, 2018)
The study aimed to identify the level of implementing the dimensions of smart organization at the Palestine Technical College of Deir al-Balah to, and the level of achievement of the characteristics of technical innovation from the staff's perspectives. It also aimed to identify the differences in the respondents' responses with regard to their views on the smart organization and its role in the creation of technical innovation in college due variables (age, years of service, academic level, job title). The study sample was selected using a comprehensive survey method so as to include all academic and administrative staff (except for the category of services) in college. The total number was (147) employees. To collect data, two research instruments were designed: a questionnaire and an interview. The researchers used descriptive and analytical approach. The study results revealed the following: The level of implementing the concept of smart organization at college was medium; the business intelligence standard in the college was achieved by 60.60%, decision making and support of the competitive position was 61.54%; the creative trend was (61.88%); and the technical innovation dimension achieved a relative weight of 63.24%. Furthermore, there was an impact of the Smart Organization in the creation of technical innovation in Palestine Technical College. Finally, there were medium significant differences between the respondents' responses with regard to their views on the smart organization and its role in the creation of technical innovation in Palestine Technical College due to (age, years of service). However, no differences were attributed to the variables of academic level and job title. Keywords: Smart Organization, Technical Innovation, Business Intelligence.